Implementasi Kebijakan Pembangunan Zona Integritas Menuju Wilayah Bebas Korupsi dan Wilayah Birokrasi Bersih - Germana A.M. Loro; Romli Arsad; Tun Huseno (Syntax Idea)
Government bureaucracy plays a crucial role in supporting the national administrative system as it is responsible for performing public service functions, empowering communities, and contributing to national development. The bureaucracy in Indonesia currently faces several issues, such as administrative personnel not being entirely clean and accountable, administrative inefficiency, poor quality public services, and quantity falling short of expectations. The objective of this research is to identify and analyze the implementation of the policy on developing integrity zones towards corruption-free areas and clean-serving bureaucracies in the Manokwari District Court. This study utilizes a qualitative method with a descriptive approach. Data collection methods include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. The theory used in this research is Edward III's policy implementation model, consisting of four variables: communication, resources, disposition, and bureaucratic structure. The research findings indicate that the development of integrity zones has been implemented in the Manokwari District Court but has not yet received the predicates of a Clean and Serving Bureaucracy (WBK/WBBM). This is due to several obstacles, such as bureaucratic culture and mindset, insufficient human resources, budget limitations, and facilities. Based on these findings, it is recommended that all employees participate in the implementation of bureaucratic reform towards WBK/WBBM and integrity zones in the Manokwari District Court. This effort should be continually maximized, not only to obtain the WBK/WBBM predicates but also as a means to enhance services to justice seekers and eliminate corrupt behavior.